2016
DOI: 10.1186/s12941-016-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing pathogen identification in patients with meningitis and a negative Gram stain using the BioFire FilmArray® Meningitis/Encephalitis panel

Abstract: BackgroundMeningitis with a negative cerebrospinal (CSF) Gram stain represents a diagnostic and therapeutic challenge. The purpose of our study was to evaluate the performance of the BioFire FilmArray® Meningitis/Encephalitis (FA ME) panel in patients presenting with community-acquired meningitis with a negative Gram stain.MethodsCSF from 48 patients with community-acquired meningitis with a negative Gram stain admitted to four hospitals in Houston, TX underwent additional testing by the FA ME. FA ME results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 19 publications
(21 reference statements)
6
38
6
Order By: Relevance
“…Our study also confirms recent findings that viral meningitis can present with neutrophilic pleocytosis that is more common in children with enterovirus infection [16]. Identifying viral causes with a rapid PCR test could potentially avoid or decrease the length of stay in the majority of cases [17]. Overall, we found that the original definition of aseptic meningitis still holds true as does the assertion that patients afflicted with this disease process have generally good outcomes, aside from possible neuropsychological sequelae, despite the diagnostic and treatment choices done by clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…Our study also confirms recent findings that viral meningitis can present with neutrophilic pleocytosis that is more common in children with enterovirus infection [16]. Identifying viral causes with a rapid PCR test could potentially avoid or decrease the length of stay in the majority of cases [17]. Overall, we found that the original definition of aseptic meningitis still holds true as does the assertion that patients afflicted with this disease process have generally good outcomes, aside from possible neuropsychological sequelae, despite the diagnostic and treatment choices done by clinicians.…”
Section: Discussionsupporting
confidence: 90%
“…While the RT-PCR assays included in the study had limited coverage compared to some of the commercial assays, it is likely that these assays have the potential to identify the majority of meningitis cases at a much lower cost [19] [18]. Although currently RT-PCR assays are typically performed in large centralised laboratories, future developments in point of care testing may facilitate the devolution of testing to smaller hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the development of multiplex RT-PCR assays provides the opportunity to detect multiple potential pathogens simultaneously[1118]. Such multiplex RT-PCR assays can offer a very comprehensive panel of potential pathogens allowing for an extensive and exhaustive investigation of patients with suspected meningitis[19, 20]. However, in practice in specific geographic settings and in particular patient population groups, a far more limited number of pathogens constitute the vast majority of cases of meningitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrated FilmArray system has a turnaround time of about an hour, with only 2 minutes of hands-on time. At the time of the manuscript preparation, two studies have reported on the performance of this assay 79, 80 . Using 48 samples from gram stain negative CSF samples from suspected cases of meningitis, Wootton et al showed that this system detected more viral pathogens especially EBV.…”
Section: Molecular Methods In Diagnosis Of Cns Infectionsmentioning
confidence: 99%